PENGARUH BIMBINGANBELAJAR WALI KELAS TERHADAP MOTIVASI BELAJAR SISWA MADRASAH TSANAWIYAH ARRISALAH SLAHUNG PONOROGO - Wahyu Eka Erliyantina; Nurul Iman; Sigit Dwi Laksana (TARBAWI:Journal on Islamic Education, 2020)
This study aims to find out how students’ tutorial activities with homeroom teachers. To find out how much influence homeroom teacher tutoring on student motivation in Madrasah Tsanawiyah Arrisalah. This type of research used in this study is quantitative research. The subject of this study were all VII-IX in Madrasah Tsanawiyah Arrisalah, graders consisting of 8 classes with a total of 139 students. The research method used is the method of data collection using questionnaires, interviews and documentation. While the analysis using the SPSS 17 application to determine the resulteof the data that has been done. The result of this study can be concluded that the activities of tutoring with the homeroom teacher proved effective in helping students increase student motivation enthusiasm for learning. This is based on data processing which states that there is a significant influence between the tutor classroom tutoring activities on student learning motivation in Madrasah Tsanawiyah Arrisalah school year of 2018/2019 with influence of 35,5% while 64,5% student motivation is influenced by other factors hot mentioned and has not been revealed in this study.